Tribology of ceramics and composites : a materials science perspective - Basu, Bikramjit (Wiley, 2011)
This book helps students and practicing scientists alike understand that a comprehensive knowledge about the friction and wear properties of advanced materials is essential to further design and development of new materials. With important introductory chapters on the fundamentals, processing, and applications of tribology, the book then examines in detail the nature and properties of materials, the friction and wear of structural ceramics, bioceramics, biocomposites, and nanoceramics, as well as lightweight composites and the friction and wear of ceramics in a cryogenic environment.
Keywords: Ceramic materials -- Mechanical properties.; Ceramic materials -- Fatigue.; Mechanical wear.; Friction.; Tribology.; elektronické knihy; electronic books